A visão do cosmo no “Tratado da magia” de Giordano Bruno - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This study aims to elucidate the magical cosmos of Giordano Bruno (1548-1600), Italian philosopher, presents the work in the Treaty of magic, from a discussion of the concepts of place and magic in Renaissance historiography, seeking to situate the Treaty of magic in the long term, according to long-term middle age of Jacques LeGoff. In this research are also discussed the question of philosophy and magic of Bruno, inserted in the broader context of Renaissance Europe. The medieval notion of nature and the vision of the cosmos inside the Treaty of magic are some of the issues are discussed in this dissertation.
Keywords: Renascença; Estudo de Giordano Bruno; CIÊNCIAS HUMANAS: HISTÓRIA